2015
DOI: 10.3233/wor-152118
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic assessment for the task of repairing computers in a manufacturing company: A case study

Abstract: This assessment found ergonomic risks mainly in the trunk, arm/forearm, and legs; the neck and hand/wrist were also compromised. Opportunities for ergonomic analyses and interventions in the design and execution of computer repair tasks are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Similarly, previous studies have shown that computer related tasks can cause neck pain and low back pain [22]. Neck pain was associated with low or high screen position while shoulder symptoms were associated with high position of mouse and poor placement of keyboard [9,17,24]. MSK discomforts in shoulder, neck, and upper back can be reduced by raising computer users' knowledge regarding sitting posture and workstation [14,19].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Similarly, previous studies have shown that computer related tasks can cause neck pain and low back pain [22]. Neck pain was associated with low or high screen position while shoulder symptoms were associated with high position of mouse and poor placement of keyboard [9,17,24]. MSK discomforts in shoulder, neck, and upper back can be reduced by raising computer users' knowledge regarding sitting posture and workstation [14,19].…”
Section: Discussionmentioning
confidence: 79%
“…MSK symptoms in computer users are believed to have multi-factorial causes. It consists of non-neutral wrist, poor postures of arms and neck, poor work-station design, and duration of working on computer as well as psychological and social factors [8,9].Some researchers have reported that higher level of prevalence of MSK symptoms is linked with increased use of mouse [10,11]. Poor posture can lead to structural deformation of body, development of muscular contractures, discomfort in back and legs, decreased capacity of lungs, poor circulation, intravascular pressure and other irregularities [5,12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods and assessment tools [6] have been developed to facilitate the understanding and evaluation of the stresses and strains observed by a working body operating in an occupational workstation. Some of these include RULA -Rapid Upper Limb Assessment [7], REBA -Rapid Entire Body Assessment [8], and ROSA -Rapid Office Strain Assessment [3].…”
Section: Methodsmentioning
confidence: 99%
“…The application of REBA in manufacturing technology is defined by activities such as computer repair [77] or the manufacturing of electrical products [86]. In addition, it was combined with other methods such as OCRA to study the ergonomic assessment of electric motor assembly line operators [69].…”
Section: Technologymentioning
confidence: 99%